Rheological Properties and Thermal Conductivity of Epoxy Resins Filled with a Mixture of Alumina and Boron Nitride - Van-Dung Mai (Polymers, 2019)
Electronic packaging materials with high thermal conductivity and suitable viscosity are necessary in the manufacturing of highly integrated electronic devices for efficient heat dissipation during operation. This study looked at the effect of boron nitride (BN) platelets on the rheology and thermal conductivity of composites based on alumina (Al2O3) and epoxy resin (EP) for the potential application as electronic packaging. The viscosity and thermal conductivity of the composite were increased upon increasing filler content. Furthermore, thermal conductivity of the BN/Al2O3/EP was much higher than that of Al2O3/EP at almost the same filler loadings. These unique properties resulted from the high thermal conductivity of the BN and the synergistic effect of the spherical and plate shapes of these two fillers. The orientation of BN platelets can be controlled by adjusting their loading to facilitate the formation of higher thermally conductive pathways. The optimal content of the BN in the Al2O3/EP composites was confirmed to be 5.3 vol %, along with the maximum thermal conductivity of 4.4 W/(m·K).